Wheat and barley dehydrins under cold, drought, and salinity – what can LEA-II proteins tell us about plant stress response? - Kosová, Klára; Vítámvás, Pavel; Prášil, Ilja T. (Frontiers in Plant Science, 2014)
Dehydrins as a group of Late embryogenesis abundant II (LEA-II) proteins represent important dehydration-inducible proteins whose accumulation is induced by developmental processes (embryo maturation) as well as by several abiotic stress factors (low temperatures, drought, salinity). In the review, an overview of studies aimed at investigation of dehydrin accumulation patterns at transcript and protein levels as well as their possible functions in common wheat (Triticum aestivum), durum wheat (Triticum durum) and barley (Hordeum vulgare) plants exposed to various abiotic stress factors (cold, frost, drought, salinity) is provided. Possible roles of dehydrin proteins in an acquisition and maintenance of an enhanced frost tolerance are analysed in the context of plant developmental processes (vernalization). Quantitative and qualitative differences as well as posttranslational modifications in accumulated dehydrin proteins between barley cultivars revealing differential tolerance to drought and salinity are also discussed. Current knowledge on dehydrin role in wheat and barley response to major dehydrative stresses is summarized and the major challenges in dehydrin research are outlined.